Variations in the Field of View of the Forensic Artist’s Workspace in Constructing Facial Composites by Video Calls (2018)
Introduction: This article presents the results of an already completed study, whose aim was to determine whether, during the construction of facial composites by video calls, there is a possible correlation between the extent of the field of view that the witness or victim has with respect to the forensic artist’s workspace, and the resulting resemblance between the sketch and the face of the person to be identified. Approach: Emphasis is put on the applicability of these new technological means in the Latin American context, particularly towards overcoming the physical distances between victims and judicial authorities of some countries in the region. Method: A first group of 24 volunteers located in Santiago de Chile took part in individual cognitive interviews with a forensic artist settled in Dundee (United Kingdom) by video calls, 24 hours after having briefly observed the photograph of a character in a British TV series not broadcasted in Chile. During the interviews, 12 of them had visual access to the image of the artist’s upper trunk and workspace, while the other 12 only observed a white wall on the screen. Subsequently, a second group of 24 individuals, also located in Chile, assessed the resemblance between sketches and original images using a Likert scale. Results: The data obtained suggest that there is no direct correlation between the variables considered, implying that changes in the environment of interviews would not have a significant effect on the construction of facial composites. Conclusion: The illusion of copresence seems not to be imperative for building rapport between the interviewee and the forensic artist.